Risk-Based Maritime Regulation in Developing Economies: The Convergence of Law and Insurance (Journal of Advances and Scholarly Researches in Allied Education, 2025)
In an increasingly interconnected global economy, maritime transport remains the backbone of international trade, accounting for over 80% of global cargo movement (Stopford, 2009). For developing economies, maritime governance is not merely a matter of compliance with international norms but a core determinant of national economic growth, security, and environmental sustainability. Yet these states often grapple with limited institutional capacity, regulatory fragmentation, and rising exposure to maritime risks such as piracy, environmental disasters, and supply chain disruptions. This article examines the evolution, rationale, and practice of risk-based maritime regulation an approach that prioritizes the assessment and mitigation of risk over reactive and prescriptive rule enforcement. The paper articulates how legal frameworks and marine insurance mechanisms converge in developing economies to manage risk, allocate liability, enhance compliance, and mobilize financial resilience. Drawing on historical development, international perspectives, case examples, and theoretical insights, our study underscores the need for harmonized, adaptive, and collaborative frameworks that align legal standards with risk-informed regulatory strategies. The analysis concludes with recommendations for policymakers, insurers, and maritime stakeholders to bridge capacity gaps, integrate risk assessment tools, and foster resilient maritime sectors.